Keefektifan Model Realistic Mathematics Education Berbantuan Media Dakon Terhadap Hasil Belajar Perkalian - Novy Trisnani; Elok Fariha Sari (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
This study aims to test the effectiveness of Realistic Mathematics Education (RME) model with ‘dakon’ media for multiplication operations of 4th grade elementary school learning outcomes in Srikandi Gunungpati Semarang. This is a quasi experimental research with a non-equivalent control group design. The sampling technique is cluster or area sampling, which specified to Pongangan Elementary School as an experimental class and Cepoko Elementary School as a control class. The data was collected with test and non-test techniques. The results showed an increase in student learning outcomes in the experimental class by 37,06 and the control class by 32,88. The hypothesis test results showed the value of t-count (2.32)> t-table (1.67), so that the average learning outcomes of the experimental class multiplication operations was higher than the average learning outcomes of the control class. Furthermore, the n-gain of the experimental class was 0.69 with high criteria and the n-gain value of the control class was 0.63 with moderate criteria. From the gain and n-gain values, the increase in learning outcomes in the experimental class was higher than the control class in medium improvement category. Based on these results, it can be concluded that the RME learning model with dakon media is more effective in improving learning outcomes than the conventional model in multiplication learning of 4th grade students at elementary school of Cluster Srikandi Gunungpati Semarang.